Source-grid-load-storage interactive power quality characteristic of active distribution network - Li, Yahui; Lou, Jie; Sun, Kaiqi; Li, Ke-Jun (Frontiers in Energy Research, 2022)
Source-grid-load-storage has represented an interactive characteristic in the active distribution network (ADN). Moreover, power electronic devices have been widely used for source-grid-load-storage with the rapid development of power electronics technology. In this condition, the large-scale distributed source may cause voltage quality degradation, while the application of large-scale power electronics equipment may also lead to serious harmonic distortion. Power quality has become one of the most important issues in the development of ADN. In this paper, the source-grid-load-storage interactive power quality characteristic of the ADN is analyzed. Firstly, considering the source-grid-load-storage interaction in ADN, the voltage deviation and fluctuation are analyzed and the degrees are further quantified. Then, the source-load-storage harmonic models for the power electronic components are built, which is the basis for harmonic analysis. Moreover, the decoupled harmonic power flow algorithm for ADN is proposed to analyze the system harmonic distributions. Finally, considering the location and capacity of photovoltaic and energy storage, the interaction and power quality are analyzed in the IEEE 33-bus distribution system. With the access of energy storage, more than 20% of the voltage deviation and more than 6% of the voltage fluctuation caused by photovoltaics are effectively suppressed, while the harmonic distortion may be further increased.